THE EFFECT OF DIALOGUE COMPLETION TASKS AND ORAL QUESTIONNAIRE TO READING COMPREHENSION - TRIMEY LIRIA HUTAURUK (JURNAL ILMIAH MAKSITEK, 2020)
The objective of this research is to find the empirical evidence of the differences between by using the Mind-Mapping, Smallgroup, and Conventional to the ability at Group C and Group D of Semester II of Nursing Academy of North Tapanuli with thetotal number was 32 and 33 in each group. The subject was given pre-test before treatment. Then the student of experimentgroup was taught by using Mind-Mapping and Small group discussion method to teaching comprehension. Finally, the writergave post-test to experiment group. The writer used t-test formula, and (Two Way - ANOVA). This is an experimentalresearch and the research used quantitative approach in finding out the answer of the problem study. The sample of thestudy was Students of Semester II of Nursing Academy of North Tapanuli. Therefore, to reading comprehension which istaught by using Mind-Mapping method, is better than the students' reading achievement which is taught by using SmallGroup discussion, Conventional teaching. Finally, based on the finding of the research, the writer gave some suggestions.She hopes this research will be useful for improving of education in Indonesia.